ANALYSIS OF SOCIAL INTEREST THEORY RELATED TO EARLY MARRIAGE IN KEBOMAS DISTRICT, GRESIK - Laili, Dinda Faizatul; Waasinas, Aby Isnain Naafie; Fajriyah, Intan Nur; Rifqi, Muhammad Jazil (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
AbstrakEarly marriage is one of the issues highlighted by the Indonesian government today. It is undeniable that the trend of early marriage, especially in rural communities, has increased significantly in contrast to urban communities. Many factors are behind it such as economic factors, social conditions, and traditions that certainly have a big impact on this trend. The author is interested in analyzing the case by using the Pound theory of social interest, especially in terms of health insurance, safety, security and order. The purpose of this study was to analyze whether the practice of early marriage in Kebomas District has been able to be covered in the Pound theory of social interest, and whether the standards are appropriate. In conducting the research, the author uses qualitative research with sociological approach with interviews and observations as a data collection technique. The results of this study showed that early marriage in Kebomas district showed that most had met the assurance standards set forth by Pound. However, the efforts of Kua Kebomas that are not balanced by the awareness of the local community are also a problem so that there are still people who do not understand the importance of marriage on time.Keywords: early marriage, Social Interest, factors of early marriage